2021
DOI: 10.3390/molecules26175192
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Ameliorates Scopolamine-Induced Cognitive Dysfunction and Neuronal Damage in Mice

Abstract: We investigated the protective effect and mechanisms of apigenin against cognitive impairments in a scopolamine-injected mouse model. Our results showed that intraperitoneal (i.p.) injection of scopolamine leads to learning and memory dysfunction, whereas the administration of apigenin (synthetic compound, 100 and 200 mg/kg/day) improved cognitive ability, which was confirmed by behavioral tests such as the T-maze test, novel objective recognition test, and Morris water maze test in mice. In addition, scopolam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 74 publications
2
9
0
Order By: Relevance
“…Treatment with donepezil significantly reversed Scop-induced effects and managed to diminish the pro-apoptotic Bax mRNA level and the Bax/Bcl2 ratio and to increase the anti-apoptotic Bcl2 mRNA level. These results are consistent with the previous results [ 87 , 88 ]. The administration of TN extract (100 and 200 mg/kg) decreased the Bax mRNA overexpression, while all doses of TN extract (50, 100 and 200 mg/kg) promoted the Bcl2 mRNA expression, thus reducing the Bax/Bcl2 ratio, which indicates an anti-apoptotic effect.…”
Section: Discussionsupporting
confidence: 94%
“…Treatment with donepezil significantly reversed Scop-induced effects and managed to diminish the pro-apoptotic Bax mRNA level and the Bax/Bcl2 ratio and to increase the anti-apoptotic Bcl2 mRNA level. These results are consistent with the previous results [ 87 , 88 ]. The administration of TN extract (100 and 200 mg/kg) decreased the Bax mRNA overexpression, while all doses of TN extract (50, 100 and 200 mg/kg) promoted the Bcl2 mRNA expression, thus reducing the Bax/Bcl2 ratio, which indicates an anti-apoptotic effect.…”
Section: Discussionsupporting
confidence: 94%
“…Groups treated with risperidone or apigenin or silymarin showed significant increases in alternation score. This impact is agreed with preceding research (22)(23)(24) that observed that risperidone, apigenin and silymarin enhanced the behavior in T-maze.…”
Section: Discussionsupporting
confidence: 93%
“…The scopolamine was dissolved in normal saline and administered intraperitoneally using an insulin syringe. Group III and IV: received donepezil (1 mg/kg/day) or CPO (100 mg/kg/day, as an emulsion form using distilled water containing 10% Tween 80), respectively, orally a week before scopolamine challenge, then concomitantly with scopolamine (1.5 mg/kg/day, intraperitoneally) [ 26 ] for another week.…”
Section: Methodsmentioning
confidence: 99%